Characteristics of Lymphoma in Patients with Inflammatory Bowel Disease: A Systematic Review. (19th September 2020) - Muller, Marie; Broséus, Julien; Feugier, Pierre; Thieblemont, Catherine; Beaugerie, Laurent; Danese, Silvio; Arnone, Djésia; Ndiaye, Ndeye Coumba; Kokten, Tunay; Houlgatte, Rémi; Peyrin-Biroulet, Laurent
Abstract: Background: Lymphoma is a dreaded complication of inflammatory bowel diseases [IBD]. Knowledge about lymphoma in patients with IBD is limited to epidemiological data and the description of risk factors. We performed a systematic review to describe the clinical characteristics and prognosis of lymphoma in patients with IBD. Methods: Electronic databases were searched up to June 1, 2020. All published clinical characteristics of lymphoma occurring in patients with IBD were collected. Results: Eleven studies were included. A total of 589 lymphomas were described in patients with IBD. As seen in de novo lymphoma, non-Hodgkin's lymphoma [NHL] was the most common histological subtype [83.9%]. Diffuse large B-cell lymphoma [DLBCL] and follicular lymphoma were the most well-represented NHL in patients with IBD [30% and 13% respectively]. Two main differences were observed in comparison with de novo lymphoma: primary intestinal lymphoma [PIL] represented a large proportion of lymphoma in patients with IBD [22–75%] whereas mucosa-associated lymphoid tissue [MALT] lymphoma was under-represented. Epstein–Barr virus [EBV]-positive status was observed in a large proportion of tumours [44–75%]. Survival data of lymphoma in patients with IBD were similar to those of de novo lymphoma. Discussion: This systematic review first highlights that PIL [especially DLBCL subtype] is significantly more frequent in patients with IBD and represents the most common entity. Conversely, MALT lymphoma is extremely rare in the IBD population. However, the overall quality of the evidence is low. Further studies are required to better define lymphoma characteristics in patients with IBD.